Baxada Classicists: The Development of Classical Studies in Paraná (1960-1980) (Circe de clásicos y modernos, 2023)
This article examines the development of Hellenic studies in the city of Paraná during the 1960s and 1970s. It was a stage characterized by the presence, in the capital of Entre Ríos, of a number of individuals who in one way or another contributed to promoting the study and teaching of classical Greek culture. Along these lines, the intellectual trajectories and academic networks of these scholars are the focus of this research. Emphasis will be placed on the figures of Osvaldo Melella and Vicente Visñovezky, for the field of Literature, Juan Carlos Wirth for the domain of History, and Celia Ortiz de Montoya for Philosophy. Finally, this study seeks to uncover the reasons that led to a loss of interest in classical studies in the academic communities in the 1980s and 1990s.
Keywords: Classical studies; Paraná; University of Entre Ríos; Teachers Institute